Preliminary displacement-based assessment procedure for buildings on liquified soil - Maxim Millen (2018)
This paper provides a simple preliminary procedure for estimating the performance of a building on liquefiable soil. The procedure directly accounts for damage related to ground shaking and in-directly accounts for settlements. Additionally, it also considers the change in shaking demand and changes to the natural vibration modes of the systems due to liquefaction. The proposed procedure makes use of a displacement-based assessment procedure that considers nonlinear soil-foundation-structure interaction and extends it to include the effects of liquefaction. The extensions rely on several assumptions about the behaviour of the soil, site response and the structure, which require further research to improve the robustness of the assessment. Two small studies are conducted: one explores at what time the peak displacement of a system occurs during shaking, and the second explores the potential changes in site amplification due to liquefaction, which provide some justification to the proposed assumptions for the procedure. The procedure is applied to a six-storey two-bay case study reinforced concrete frame building to demonstrate the influence of various effects of liquefaction. For the case study building, the role of shaking damage was large and the estimated reduction in shaking demand was important to the estimated level of ductility demand, highlighting the importance of quantifying the expected site response for the assessment of building performance.